Analisis Kepuasan kerja berdasarkan Aspek Komunikasi, Motivasi dan Lingkungan Kerja (Studi pada Pegawai Bawaslu Kabupaten Pidie Jaya) - Hayatun Nufus, Cut; Fauzi, Fauzi; Mirza, Mirza (Singkite Journal, 2024)
The study aims to analyze employee job satisfaction based on aspects of communication, motivation and work environment conducted with a case study on Bawaslu employees of Pidie Jaya Regency. The study applies an associative method with a quantitative approach by inferencing with path analysis. The sample in this study was all Bawaslu employees totaling 40 people. The results of the study are known, 1) There is an influence of communication, motivation and work environment factors directly on employee job satisfaction, respectively by 38.54%, 58.32% and 33.76%. 2) Simultaneously communication, motivation and work environment affect employee job satisfaction by 54.1%.